Implementation of the Ziegler-Nichols Proportional Integral Derivative (PID) Method on Coffee Bean Roasting Machine Controls - Nggala, Liberius Harsen; Nachrowie; Subairi (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2023)
PID  control  has  been  used  in  simple  or  complex  machine  control.  Coffee  is  an  agricultural  commodity  that  is widely used as a food and beverage ingredient. Coffee bean roasting is required before it can be further processed (consumed).  This  research  was  conducted  to  create  an  automatically  controlled  coffee  bean  roaster  using  the Ziegler-Nichols type-1 PID method. This coffee bean roaster is made with a series of roasters, DC motors, servo motors, ESP32, thermocouple sensors, load cell sensors, ceramic stoves, and other supporting components. The bitterness variations of the coffee beans produced are "light" (3-5% moisture content), "medium" (5-8% moisture content), and "dark" (8-12% moisture content). The Ziegler-Nichols PID control is implemented on this machine to control the degree of rotation of the gas faucet servo motor on the stove so that the temperature in the roasting pan matches the specified set point. Based on the results of the research that has been done, the implementation of PID control was successfully carried out at the temperature set point used, 145 ̊C with a 7,2 KP value, a 0.034 KI value, and a 413.6 KD value. The research tools measurement’s average error was 0.32% for temperature, and 0.24% for weight.